The Forbidden Book of the 18th c.: Count Nikolaus Ludwig von Zinzendorf’s „Stebuklingo Meile warginga Griekininko=Sʒirdis“ (1752) - Strungytė-Liugienė, Inga (Knygotyra, 2020)
This article studies the Lithuanian treatise „Stebuklingo Meile warginga Griekininko=Szirdis priesz Jezaus kruwinos Ronus“, published in 1752 and currently stored in Berlin, in the Secret Archive of Prussian Cultural Heritage. Questions are raised regarding the attribution of the original version as well as the translation of the treatise, its composition and contents are discussed. The article provides the historical context of the 18th c. as well as the penetration of the Moravian movement and its attempts to consolidate within Prussian Lithuania. It was determined that the treatise is a Lithuanian translation of a theological treatise written by Count Nikolaus Ludwig von Zinzendorf (1700–1760), leader of the Moravian movement, and titled „Die erstaunliche Verliebtheit eines armen Sünder-Herzens gegen die blutigen Wunden Jesu“. This publication is unknown to book historians and is not registered in Lithuanian bibliographical issues. The translation was most probably done by Adam Friedrich Schimmelpfennig the Younger (1699–1763), Priest of Papelkiai, a well-known author of Prussian Lithuania, editor of the Lithuanian Bible (1755), translator of religious hymns and compiler of the official Evangelical Lutheran Church hymnal (1750).
Keywords: Moravian movement; Nikolaus Ludwig von Zinzendorf; treatise „Stebuklingo Meile warginga Griekininko=Sʒirdis; Die erstaunliche Verliebtheit eines armen Sünder-Herzens gegen die blutigen Wunden Jesu“; Zinzendorf ’s theology, Adam Friedrich Schimmelpfennig the Younger (1699–1763); Prussian Lithuania in the 18th century